Fostering sustainable careers across the lifespan: The role of disability, idiosyncratic deals and perceived work ability - Brzykcysg,Anna; Boehm,Stephan; Baldridge,David (Journal of Vocational Behavior, 2019)
While scholars and practitioners are increasingly aware of the positive effect of idiosyncratic deals (i-deals) on employee attitudes, little is known about how i-deals might affect work and career outcomes for employees with disabilities, a marginalized and understudied group. The present study builds on Conservation of Resources (COR) theory to explain how i-deals might influence perceived work ability for employees with disabilities, and in turn, their turnover intentions. Furthermore, this study is the first to compare the experiences of employees with physical, psychological and no disabilities regarding these relationships. Our hypotheses are tested using field data from 19,770 employees working for a German federal agency. In brief, the negative direct effect of i-deals on turnover intentions is found to be stronger for employees with physical disabilities than for those without disabilities. Further, the results indicate a significant negative indirect effect of i-deals on turnover intentions through perceived work ability for all employee groups. As expected, we find that this indirect effect increases in magnitude when going from the condition having a physical disability or no disability to the condition having a psychological disability. Implications for research, theory and practice are discussed.
Keywords: Management